Molecular imaging of dementia - MORI, Takaaki; MAEDA, Jun; SHIMADA, Hitoshi; HIGUCHI, Makoto; SHINOTOH, Hitoshi; UENO, Shu-ichi; SUHARA, Tetsuya (Psychogeriatrics, 2012)
Diagnosis and treatment strategies for dementia are based on the sensitive and specific detection of the incipient neuropathological characteristics, combined with emerging treatments that counteract molecular processes in its pathogenesis. Positron emission tomography (PET) is used for diverse clinical and basic studies on dementia with a wide range of radiotracers. Approaches to visualize amyloid deposition in human brains non‐invasively with PET depend on imaging agents reacting with amyloid fibrils. The most widely used tracer is [11C]‐6‐OH‐BTA‐1, also known as Pittsburgh Compound‐B, which has a high affinity to amyloid β peptide (Aβ) aggregates. Some 18F‐labeled amyloid ligands with a longer radioactive half‐life have also been developed for broader clinical applications. In addition, there have been demonstrated advantages of tracers with high specific radioactivity in the sensitive detection of amyloid, which have indicated the significance of Aβ‐N3‐pyroglutamate as a new diagnostic and therapeutic target. Furthermore, beneficial outcomes of Aβ and tau immunization in humans and mouse models have highlighted crucial roles of immunocompetent glia in the protection of neurons against amyloid toxicities. The utility of PET with a radioligand for translocator protein as a biomarker for tau‐triggered toxicity, and as a complement to amyloid and tau imaging for diagnostic assessment of tauopathies with and without Aβ pathologies, has also been demonstrated. Meanwhile, brain cholinergic function can be estimated by measuring acetylcholinesterase activity in the brain with PET and radiolabeled acetylcholine analogues. It has been reported that patients with early Parkinson's disease exhibit a reduction in acetylcholinesterase activity in the cerebral cortex, and this decline is more profound in patients with Parkinson's disease with dementia and dementia with Lewy bodies than in patients with Parkinson's disease without dementia. The Alzheimer's Disease Neuroimaging Initiative was a multicentre research project conducted over 6 years that studied changes in cognition, brain structure, and biomarkers in healthy elderly controls and subjects with mild cognitive impairment and Alzheimer's disease. An international workgroup of the National Institute on Aging‐Alzheimer's Association has suggested that Alzheimer's disease would be optimally treated before significant cognitive impairment, defined as a ‘presymptomatic’ or ‘preclinical’ stage. Therefore, PET will be of technical importance for both clinical and basic research aimed at prodromal pathologies of Alzheimer's disease.